Resilient Urban Design Approach for Coastal Settlement (Case Study: Kampung Bahari Tambak Lorok, Semarang) - Khansa Saffana; Febri Guinensa Putra; Ananda Amelia Pandani; Heru Wibowo Poerbo (TATALOKA, 2023)
Kampung Bahari Tambak Lorok is a coastal settlement in Semarang that has a vulnerability to disaster. The main problem of the vulnerability is the tidal and annual flooding every rainy season. The flooding is caused by the location of Kampung Bahari, the land subsidence issue, and the effect of climate change that causes extreme weather and sea-level rise (SLR). Kampung Bahari is located in North Semarang and is formed by the young alluvial deposits that trigger subsidence, while the subsidence itself is not only caused by geology reason but also geotechnical reasons, such as excessive water consumption, consolidation, and excessive land loads. This paper aims to examine the design approach that is most probable to be implied due to the vulnerability of Kampung Bahari towards the tidal and annual flood caused by the reasons mentioned above. The research will be carried out by data collection about Kampung Bahari, finding the actual settlement condition, and describing the problems deeper. The result will focus on the physical intervention consisting of implementing water-sensitive design principles, especially in the spatial planning of the settlements, urban system efficiency, building prototype guidelines, and infrastructure.